Funkcje żłobków polskich od zakończenia II wojny światowej do początków XXI wieku na przykładzie żłobków lubelskich - Świdrak, Ewelina (Biuletyn Historii Wychowania, 2023)
Nurseries in Poland are over 100 years old. Since the beginning of their existence, before Poland regained independence, until present days they have changed their functions and organization. The aim of the article is to show crèches changed against the political, social and cultural background of the end of the Second World War to the early 21st century. The method used in this article is a historical monograph, and the technics include an analysis of generally accessible documents (literature, magazines for women, legal acts, films) and an analysis of personal documents of retired nursery workers. The documentation has been supplemented by 10 interviews with ladies employed in Lublin nurseries from 1973 until 2019. The article has been written in cooperation with the Municipal Nurses Complex in Lublin. The tasks of crèches as presented in this article are care, pro-professional, prohealth, educational, upbringing and family function. This article is the second part of two articles, which concerns changes in the function of crèches in their history. The first part is published in “Bulletin of the History of Education” in 2019.